The Effect of Question-Answer Relationship (QAR) Strategy on Islamic Junior High School Students’ Reading Comprehension in Recount Texts - Moh. Ramadhani Rakhmatulloh; Asrori Asrori (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to investigate the effectiveness of the Question-Answer Relationship (QAR) strategy on students’ reading comprehension of recount texts among eighth grade students at an Islamic junior high school in Surabaya in the academic year of 2025/2026. The study focused on examining students’ improvement in reading comprehension after the implementation of the QAR strategy. Pre-tests and post-tests were administered to measure students’ performance before and after the treatment. The data were analyzed using SPSS, and since the data were not normally distributed, the Wilcoxon Signed Ranks Test was used as the hypothesis test. Effect size analysis was also conducted to determine the strength of the treatment effect. The results showed that there was a significant improvement in students’ reading comprehension after the implementation of the QAR strategy, as indicated by the Wilcoxon Signed Ranks Test (Z = −3.224, p = 0.001 < 0.05). The mean score increased from 69.50 in the pre-test to 76.17 in the post-test, indicating a gain of 6.67 points. Furthermore, the effect size result (r = 0.588) indicated a large effect, suggesting that the QAR strategy had a strong impact on students’ reading comprehension. In conclusion, the QAR strategy is effective in improving students’ reading comprehension of recount texts. Therefore, it can be used as an effective alternative strategy in teaching reading. Future researchers are encouraged to apply the QAR strategy in different contexts or text types, while teachers are recommended to implement this strategy to enhance students’ understanding of reading materials.